2014
DOI: 10.1128/jcm.02115-14
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Analysis of Clostridium difficile Isolates: a Single-Center Study

Abstract: f Clostridium difficile infections (CDI) are a growing concern in North America, because of their increasing incidence and severity. Using integrated approaches, we correlated pathogen genotypes and host clinical characteristics for 46 C. difficile infections in a tertiary care medical center during a 6-month interval from January to June 2010. Multilocus sequence typing (MLST) demonstrated 21 known and 2 novel sequence types (STs), suggesting that the institution's C. difficile strains are genetically diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Some strains, most notably including the epidemic strains known by their various classification schemata as ribotype 027, North American pulsed field gel electrophoresis pattern 1, or restriction endonuclease pattern BI, also produce the binary toxin, CDT (17). Although the precise pathophysiologic role of binary toxin is not known, its presence is associated with increased severity of CDI and mortality (18–20). …”
Section: Pathogenesis Of CDImentioning
confidence: 99%
“…Some strains, most notably including the epidemic strains known by their various classification schemata as ribotype 027, North American pulsed field gel electrophoresis pattern 1, or restriction endonuclease pattern BI, also produce the binary toxin, CDT (17). Although the precise pathophysiologic role of binary toxin is not known, its presence is associated with increased severity of CDI and mortality (18–20). …”
Section: Pathogenesis Of CDImentioning
confidence: 99%
“…Because AF/244 is both cdt gene positive and tcdC⌬117 positive, it has been presumptively identified as BI/NAP1/027 by commercially available NAATs (28). With use of WGS, Zhou et al additionally identified 3 unique non-BI/NAP1/027 sequence types (ST-41 and 2 novel sequence types) that are positive for tcdA, tcdB, cdtA, cdtB, and tcdC⌬117 (29). Although the stool specimens from which these isolates were derived were not tested with a NAAT designed to identify BI/NAP1/027, specimens with these genotypes would presumptively be identified as BI/NAP1/027 with the commercially available NAATs.…”
Section: Laboratory Detection Of Bi/nap1/027mentioning
confidence: 99%
“…Currently, there are no categorical interpretative criteria for ceftolozane-tazobactam MICs for Clostridium species. It is well documented that the overall antimicrobial resistance profiles of C. difficile strains can vary widely among different strain types (10)(11)(12). Unfortunately, no C. difficile strain typing data were available as part of the Snydman et al study (2), and thus it was unknown if this profile was generalizable to different C. difficile strain types.…”
mentioning
confidence: 99%
“…Of note, our test set included 26 C. difficile ribotype 027 (NAP1/BI/ST-1) strains and 3 C. difficile ri-botype 078 isolates. These strain types are currently among the most common ribotypes in North America and parts of Europe (18,19); the toxigenic status of each ribotype was determined by phenotypic (i.e., toxin enzyme immunoassays) and/or genotypic methods (3,10,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation